2018
DOI: 10.1093/occmed/kqy020
|View full text |Cite|
|
Sign up to set email alerts
|

Farming characteristics and self-reported health outcomes of Irish farmers

Abstract: This study identified self-reported patterns of risky lifestyle behaviours among particular subgroups of Irish farmers for whom targeted health interventions are warranted. Interventions are particularly important for younger farmers who may see themselves as invincible and impregnable to ill-health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…According to Table 2, all 21 studies focused on the adult population, although some samples included adolescents 26,33–37 . Most studies included both males and females in the study sample but some articles exclusively studied males or the majority of the participants were males, 33,36,38–42 a reflection of the male‐dominant farmer population. Random sampling methods were used in 7 studies, the census data were used in 2 studies, and remaining studies used convenience sampling methods.…”
Section: Farmer Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Table 2, all 21 studies focused on the adult population, although some samples included adolescents 26,33–37 . Most studies included both males and females in the study sample but some articles exclusively studied males or the majority of the participants were males, 33,36,38–42 a reflection of the male‐dominant farmer population. Random sampling methods were used in 7 studies, the census data were used in 2 studies, and remaining studies used convenience sampling methods.…”
Section: Farmer Populationmentioning
confidence: 99%
“…In general, the studies we reviewed reported a high prevalence of heavy alcohol use among farmers. For example, a study of 314 Irish male farmers found that 49.8% of respondents drank 6 or more drinks per occasion in the past month 39 . A study of 2,452 tobacco farmers in Brazil reported that 30.8% of male farmers engaged in high‐risk drinking, defined as having more than 2 doses of drinks per day 49 .…”
Section: Farmer Populationmentioning
confidence: 99%
“…As previously described [31], socio-demographic information showed that the mean age was 41.07 years (Table 1). Two-thirds (68%; n = 205) of farmers reported as being in full-time farming and engaged in a variety of farm enterprises: beef cattle/breeding cows (31%; n = 98), dairy and beef cattle (27%; n = 86), sheep (25%; n = 81), mainly beef cattle (19%; n = 59), intensive dairy (17%; n = 54), and other including tillage (19%; n = 60).…”
Section: Resultsmentioning
confidence: 65%
“…The non-probability sampling (convenience) means that the results may not be generalisable to the farming population as a whole. The socio-demographics of this study population are not representative of the national average of Irish famers [31]. Farmers with greater health problems are unlikely to be captured in the study ('healthy worker' effect).…”
Section: Limitations and Strengthsmentioning
confidence: 98%
See 1 more Smart Citation